Biochemical and functional characterization of BmooSP, a new serine protease from Bothrops moojeni snake venom. (1st March 2016) - de Oliveira, Fábio; de Sousa, Bruna Barbosa; Mamede, Carla Cristine Neves; de Morais, Nadia Cristina Gomes; de Queiroz, Mayara Ribeiro; da Cunha Pereira, Déborah F.; Matias, Mariana S.; Homi Brandeburgo, Maria Inês
Abstract: In this work, we describe the purification and characterization of a new serine protease enzyme from Bothrops moojeni snake venom (BmooSP). On SDS-PAGE, BmooSP was found to be a single-chain protein with an apparent molecular mass of 36, 000 and 32, 000 under reduced and non-reduced conditions, respectively. Mass spectrometry analysis showed that the BmooSP is composed by two isoforms with molecular mass of 30, 363 and 30, 070, respectively. The purified enzyme consists of 277 amino acid residues, disregarding the cysteine and tryptophan residues that have been degraded by acid hydrolysis, and its N-terminal sequence showed similarity with other serine protease enzymes. BmooSP induced blood-clotting in vitro, defibrination in vivo, caseinolytic and fibrin(ogen)olytic activities. The enzyme is stable at high temperatures (up to 100 °C) and shows maximum activity at pH around 7.0. Preliminary results show that BmooSP can induce the formation of a stable fibrin clot for more than 10 days. BmooSP presents medical interest because it can be used as biodegradable fibrin glue and for the treatment and prevention of cardiovascular disorders because of its ability to promote the defibrination in vivo, decreasing blood viscosity and improving blood circulation. Highlights: We describe the purification/characterisation of a new serine protease from B. moojeni (BmooSP). This protease is able to form a stable fibrin clot (fibrin glue). BmooSP can be used as tool for the study about cardiovascular disorders.